Cerdas menentukan harga jual melalui metode HPP full costing untuk womenpreneur pemula - Hayati, Cucu; Sanggarwati, Diah Ayu; Lestari, Sri; Sriwibowo, Bambang (Nur Science Institute, 2025)
This community service activity was designed to provide practical knowledge for micro business actors, housewives, and novice teenagers in determining product selling prices using the full costing method. The training was conducted through a Participatory Action Research approach, which consisted of the stages of knowing, understanding, planning, acting, and changing. Held at Jagalan Library under the auspices of the Mojokerto City Library and Archives Office in collaboration with STIE Mahardhika Surabaya, the activity offered theoretical and practical sessions. The materials delivered included a basic introduction to product selling prices with full costing method, case studies tailored to participants’ products, and simple practices. Results indicated an increase in participants’ understanding of accurate price calculation. Positive responses came particularly from housewives, many of whom had no prior business experience but expressed confidence in starting ventures. Participants also gained valuable insight into incorporating all cost components into pricing decisions for sustainable business outcomes.